Pathogenicity and performance of two candidate isolates of Metarhizium anisopliae and Beauveria bassiana (Hypocreales: Clavicipitaceae) in four liquid culture media for the management of the legume pod borer Maruca vitrata (Lepidoptera: Crambidae). (12th February 2015) - Tumuhaise, V.; Ekesi, S.; Mohamed, S.A.; Ndegwa, P.N.; Irungu, L.W.; Srinivasan, R.; Maniania, N.K.
Abstract : The aim of this study was to identify and develop entomopathogenic fungi as biopesticides for management of Maruca vitrata (Fabricius). Fourteen isolates of Metarhizium anisopliae (Metchnikoff) Sorokin and six of Beauveria bassiana (Bals.-Criv.) Vuill. were screened against first instar larvae of M. vitrata . The two most virulent isolates were selected and further tested for production in four liquid media. Different formulations of one isolate were evaluated against different developmental stages. Metarhizium anisopliae ICIPE 18 and ICIPE 69 caused highest larval mortality of 91 and 81%, with lethal time to 50% mortality (LT50 ) values of 1.8 and 1.7 days and LC50 of 1.07 × 10 7 and 3.01 × 10 6 conidia/ml, respectively. ICIPE 69 yielded more biomass and propagules in two liquid media than ICIPE 18. All developmental stages and adult moths were susceptible to fungal infection and horizontal transmission caused a significant reduction in fecundity. Isolate ICIPE 69 was identified as the most potent isolate for managing M. vitrata based on demonstrated efficacy against different developmental stages and amenability to production in liquid media and could be utilized as an alternative to pesticides in cowpea IPM.